MASSAGE STIMULATION REDUCES TUMOR NECROTIC FACTOR-ALPHA AND INTERLEUKIN-6 IN PRETERM, LOW BIRTH WEIGHT WITH APPROPRIATE GESTATIONAL AGE NEWBORNS - Trisna Windiani, I G. A.; Sotjiningsih, S.; Mantik Astawa, N.; Kusnandi,; R. (Udayana University, 2013)
Preterm newborn is susceptible from various stresses such as infections or non infections. During stress, immune response is activated by synthesizing and releasing of cytokines from activated immune cells into the circulation. One of the efforts to overcome the stress is massage stimulation. Several studies have been carried out to find out the benefit of massage stimulation. The objective of this study is to find out the effect of massage stimulation to reduce of TNF-? and IL-6 levels on preterm, low birth weight, appropriate to gestational age newborn. This was a randomized controlled trial. Subjects of the study were all preterm newborns with a stable medical condition, birth weight 1,500-2,499 gram, appropriate to gestational age. The study was carried out on October-December 2011, in neonatology ward, Sanglah General Hospital, Vali-Indonesia. The number of cases was 35 subjects and the number of controls was 36 subjects. The examination of TNF-?, IL-6 levels and birth weights before and after massage stimulation were performed on both groups. The level of TNF-? and IL-6 was examined by applying ELISA method. The level of confidence was ? = 0.05. All statistical analysis was performed by computer programme. There was different level of cytokine pro-inflammation TNF-? (p=0.025) and IL-6 (p=0,001) comparing before and after condition massage stimulation. Outcome of body weight were also different at before and after massage stimulation, with p value 0.042. The conclusion of this study is that massage stimulation can reduce the level of TNF-?, IL-6 and increasing of birth weight on preterm, low birth weight appropriate gestational age newborn. Based on this study, in the future, massage stimulation can be done in newborn with stable medical conditions by parents or trained staffs.